Corporate Sustainability in Practice: A Case Study of Employee Perspectives on Strategy Implementation - Kabykenova,Nazerke; Zvirgzdins,Agris (2025)
This thesis explores how employees influence and experience Corporate Sustainability (CS) strategy implementation at Sony. Through interviews with twelve staff members across departments, it highlights misalignment between CS goals and daily roles, and the need for clearer guidance. Bottom-up initiatives offer promise but need institutional backing. The study recommends improved communication, training, and recognition to boost employee engagement and CS effectiveness.